2017
DOI: 10.1053/j.gastro.2016.11.046
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Prediction Model to Assess Risk for Pancreatic Cancer Among Patients With New-Onset Diabetes

Abstract: Background and aims Approximately 50% of all patients with pancreatic ductal adenocarcinoma (PDA) develop diabetes mellitus before their cancer diagnosis. Screening individuals with new-onset diabetes might therefore allow earlier diagnosis of PDA. We sought to develop and validate a PDA risk prediction model to identify high-risk individuals among those with new-onset diabetes. Methods We conducted a retrospective cohort study in a population representative database from the UK. Individuals with incident di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
164
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(170 citation statements)
references
References 72 publications
5
164
0
1
Order By: Relevance
“…Recently, a clinical prediction model has been used to assess PC risk with pre-diabetic and new onset diabetic patients (Boursi et al, 2017(Boursi et al, , 2018. For pre-diabetic study, a total number of 138,232 patients with new onset impaired fasting glucose (IFG) were selected where 245 individuals were diagnosed with pancreatic ductal adenocarcinoma within 3 years of IFG diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a clinical prediction model has been used to assess PC risk with pre-diabetic and new onset diabetic patients (Boursi et al, 2017(Boursi et al, , 2018. For pre-diabetic study, a total number of 138,232 patients with new onset impaired fasting glucose (IFG) were selected where 245 individuals were diagnosed with pancreatic ductal adenocarcinoma within 3 years of IFG diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Chari et al (2005) showed that the 3-years cumulative incidence of PC among patients with new onset diabetes is 8 times higher than expected (Boursi et al, 2017). Hence, it can be stated that diabetes associated with PC may be a paraneoplastic phenomenon caused by the cancer (Pelaez-Luna et al, 2007;Sah et al, 2013;Boursi et al, 2017). Smoking also increases the risk of PC by a factor of two (American Cancer Society, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study developed and internally validated a risk prediction model for PDAC among patients with newly onset diabetes, showing the promise of risk stratification among high-risk populations. 68 The study involved 109, 385 individuals with newly diagnosed diabetes, and the outcome was PDAC diagnosed within 3 years of diabetes onset. The prediction model included demographic, behavioral, and clinical variables that were routinely collected at the time of diabetes diagnosis.…”
Section: Risk Predictionmentioning
confidence: 99%
“…Although prevalent diabetes is common in subjects >50 years of age, truly new onset diabetes is uncommon (estimates in Olmsted County range from 0.45% to 1% per year). Recently clinical risk-prediction models for PDAC in NOD have been reported but require external validation 3, 11 . There are also biomarker panels that appear promising, 12 .…”
mentioning
confidence: 99%